2021
DOI: 10.1097/j.pain.0000000000002552
|View full text |Cite
|
Sign up to set email alerts
|

A syngeneic inoculation mouse model of endometriosis that develops multiple comorbid visceral and cutaneous pain like behaviours

Abstract: A mouse model of endometriosis that recapitulates clinical features and symptoms experienced by women with endometriosis, including hypersensitivity across visceral organs, skin, and altered behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
2
9
0
Order By: Relevance
“…We then investigated whether Tsp1a could modulate pain sensitivity evoked by vaginal distension (VD) in conscious Sham control mice. In vivo vaginal pain sensitivity was monitored by measuring the VMR to increasing VD pressures using EMG electrodes surgically implanted into the abdominal muscles as previously described [16; 17; 48]. In Sham control mice, we found that VD evoked an increase in the VMR, with the degree of VMR related to the amount of pressure applied to the vagina ( Figure 3A-B ).…”
Section: Resultsmentioning
confidence: 73%
See 4 more Smart Citations
“…We then investigated whether Tsp1a could modulate pain sensitivity evoked by vaginal distension (VD) in conscious Sham control mice. In vivo vaginal pain sensitivity was monitored by measuring the VMR to increasing VD pressures using EMG electrodes surgically implanted into the abdominal muscles as previously described [16; 17; 48]. In Sham control mice, we found that VD evoked an increase in the VMR, with the degree of VMR related to the amount of pressure applied to the vagina ( Figure 3A-B ).…”
Section: Resultsmentioning
confidence: 73%
“…Further analysis revealed the VMR to non-noxious (20–30 mmHg) ( Figure 6Cii) and noxious (40– 70 mmHg) ( Figure 6Ciii) DPs were significantly enhanced in Endo mice. Endo mice displayed both allodynia and hyperalgesia, which are hallmark signs of CPP in a wide range of inflammatory diseases, including endometriosis [6; 7; 17; 47; 48; 50; 58; 62]. We then found that Endo mice treated intravaginally with Tsp1a displayed significantly reduced VMRs evoked by VD compared with Endo mice treated intravaginally with vehicle ( Figure 7A-C ).…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations